PENGEMBANGAN E-MODUL MENGGUNAKAN APLIKASI SIGIL DI KELAS V SD NEGERI 104186 TANJUNG SELAMAT - Desnica Maria Tweny Pakpahan; Nurmayani (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2023)
This research aims to develop and produce a product in the form of a feasible, practical and effective E-Module. The research method used is Research and Development (R&D) with the 4D development model (Define, Design, Development, Disseminate). The subjects in this study were material expert, media professional, education practitioners, and students of class V-B SD Negeri 104186 Tanjung Selamat. The object of this research is the E-Module using the Sigil application. The results showed that: (1) the feasibility of the E-Module was assessed by material experts with a percentage of 86.67%, and media experts with a percentage of 93%. (2) the practicality of the E-Module assessed by educational practitioners gets a percentage of 94%. (3) the effectiveness of the E-Module is assessed from the test results and student response questionnaires. The test results got a percentage of 83.40%, and the results of the student response questionnaire got a percentage of 96.65%. So it can be concluded that the E-Module using the Sigil application that was developed is declared feasible, practical, and effective for use in learning activities.